Application of MEKC to the monitoring of atrazine sorption behaviour on soils - Lima, D. L. D.
Measuring interactions between soils and xenobiotics is critical to assess the threat to water resources posed by potentially harmful chemicals. Such studies are done via batch experiments where the chemical of interest is incubated with the soil for a long period of time. However, the analysis of the remaining concentration in the aqueous phase is often troublesome, due to dissolved organic matter that can interfere with the analysis. Thus, for such application a lengthy sample clean-up is often needed prior to analysis. The aim of this work was to develop an alternative approach to monitor atrazine using MEKC. A buffer of 10 mM NaH(2)PO(4) and 50 mM SDS was used to separate atrazine and soil organic matter in less than 7 min. Samples were injected without any pre-treatment leading to a significantly lower total analysis time (sample clean-up, column conditioning, separation) than HPLC. After full optimisation, good repeatability of retention time (RSD <1%) and peak areas (RS D < 3%) was achieved as well as a good linearity (r(2) = 0.9994) and relatively low LOD (0.26 mg/L). The method was applied to study the sorption of atrazine to a soil sample using batch equilibrium technique.